Paradigma Filantropi Islam dalam Keuangan Mikro Islam: Analisis Berbasis Literatur Terhadap Fungsi Maal di Baitul Maal Wat Tamwil - Garbo, Anom (Jurnal Ilmiah Ekonomi Islam, 2025)
This study examines the incorporation of Islamic philanthropy—zakat, infaq, and sadaqah—into the operational mechanism of Islamic microfinance by specifically focusing  on the maal program in Baitul Maal Wat Tamwil (BMT). This study aims to evaluate the role of philanthropic financial instruments in ethical finance and inclusive development from an Islamic perspective. A narrative literature review with sources mostly from Scopus, as well as using Islamic microfinance and maal function in BMT as keywords, was conducted. The approach was thematic, based on the purpose of Islamic law, namely, to preserve wealth and welbeing. The study results indicated that the maal function is the base principle in Islamic microfinance rather than an extra one. Models based on institutions such as BMT and waqf-related  finance have found a successful way to blend philanthropy with financial intermediation, hence economically empowering and providing social justice. The operational impact may be improved through strategic tools such as Islamic corporate social responsibility, digital zakat platforms, and performance measurement models. This research, in refocusing maal as instrumental in sustainable microfinance, adds to Islamic finance literature. This  analysis informs policy prescriptions and institutional reforms for moral, socially inclusive financial systems in the Muslim world BMT